Design and implementation of adaptive conveyer belt for material sorting and handling assisted with image processing technology control by microcontroller - Liew, Kean Teong (2013)
Laboratory users might find themselves going crazy looking for electronic parts commingled together. The hardest part is to locate the particular part that was thrown somewhere in the container with the commingled electronic components. There are certain limitations with machines which rely much on sensors to run operations such as processes and applications. This poses limitations not only to new product development for engineers,as well as evaluation and implementation of new products. It is time consuming for engineers to perform so after everything has been completed with the aid of machine vision technology. The project consists mainly of three subsystems namely the process flow control of components, component analysis and detection as well as material sorting and handling. For the process flow of components, conveyor belt system is being implemented and applied. As for material sorting and handling, it is done by making use of the Arduino Uno as the devices to control the movement of the elevator. Right after the analysis andrecognition process is completed, the component will be allocated into its right drawer by a four axes elevator in a multi-drawer cabinet. The integration of computer control produces is a powerful tool for applications that require components recognising followed by specific allocations with the minimal level of programming involved. The innovation of thismaterial sorting and handling machine involves the consideration of priorities in terms of reliability, cost, and ease of use and simplicity. It would be a magnificent achievement in system concept in order to create commercial gadgets and as an add-onto the advancement of our technologies.